Implementasi The Concurrent Development Model Untuk Membangun Learning Management System - Novita, Rice; Munzir, Medyantiwi Rahmawita; Kurniawan, Viki (P3M Politeknik Negeri Bengkalis, 2024)
Technology plays an important role in the educational process. The weakness of the current educational process is that there is no media that helps store data, share data and monitor data properly. Learning Management System (LMS) is a web-based software program that has five main elements for management, documentation, monitoring, reporting, administration and distribution of educational content. This research aims to develop an LMS that is in accordance with the five main features in the LMS. with software development methods using The Concurrent Development Model. In this model, work activities are carried out simultaneously, each work process has several work triggers for the activity. Triggers can come from the beginning of the work process or from other triggers because each trigger will be interconnected. In system design, the concept of Object-Oriented Analysis Design (OOAD) is used with use case diagrams, activity diagrams and class diagrams.